2005
DOI: 10.1200/jco.2005.05.105
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Recurrence of Ewing’s Sarcoma Family of Tumors

Abstract: HDT as consolidation therapy for relapsed ESFT seems to be associated with improved OS, even after adjusting for RFI and response to second-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
138
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(152 citation statements)
references
References 36 publications
8
138
5
1
Order By: Relevance
“…Many studies have been conducted to assess the benefit of this megachemotherapy. Some studies suggested an improvement in clinical outcomes, [37][38][39] whereas others did not. 40,41 In the current study, HDC with hematopoietic stem cell rescue failed to improve EFS significantly among high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to assess the benefit of this megachemotherapy. Some studies suggested an improvement in clinical outcomes, [37][38][39] whereas others did not. 40,41 In the current study, HDC with hematopoietic stem cell rescue failed to improve EFS significantly among high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early exploratory studies with HDT followed by HSCT documented activity against refractory, large localized and disseminated EFT. 4,11,22 Mel has long been the most commonly used agent in HDT regimen for advanced, high-risk EFT. The French Society for Pediatric Oncology has reported excellent results in children with poor prognosis EFT who were treated with BU (600 mg/ m 2 /dose four times a day  4 days) and Mel (140 mg/m 2 , given as 70 mg/m 2 /day  2 days).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, patients with bulky primary tumors, with multifocal or metastatic disease at presentation or with refractory or recurrent disease have a very poor prognosis, with only 10-30% survival rate at 3 years. [1][2][3][4] As some studies have shown that there is a positive linear relationship between the dose of cytoreductive agents and tumor response, 5 the approach of high-dose chemo-and/or radiation therapy followed by autologous hematopoietic SCT (HSCT) has been used in the practice of treatment of EFT in an attempt to improve the disease outcome and overall survival (OS) rate. We report our experience with further intensification of treatment in children and adolescents with high-risk EFT.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 95% of Ewing's sarcomas harbor the distinctive chromosome translocation t(11;22)(q24;q12) resulting in the characteristic EWS-FLI1 fusion gene [14], a potential therapeutic target recently explored [33]. Despite the improvements in adjuvant chemotherapy, radiotherapy, and surgery, 30% to 40% of patients with Ewing's sarcoma experience disease recurrence [7,10] with only a 23% 5-year overall survival rate [4]. Approximately 20% to 30% of children with Ewing's sarcoma present with metastatic disease at diagnosis [25].…”
Section: Introductionmentioning
confidence: 99%